Reputation
Next tag badge:
98/100 score
49/20 answers
Badges
5 98 261
Newest
 Nice Answer
Impact
~1.9m people reached

Apr
24
comment Logarithmic system of equations
Using Maple. See en.wikipedia.org/wiki/Resultant
Apr
24
answered Logarithmic system of equations
Apr
24
comment Solving for $x$ after simplifying, please check my work!
You can't. That's a curve in the $x-y$ plane.
Apr
24
answered Solving for $x$ after simplifying, please check my work!
Apr
24
comment Solving for $x$ after simplifying, please check my work!
Suspiciously similar to math.stackexchange.com/questions/1248856/… although that one was looking for integer solutions.
Apr
24
answered Largest eigenvalues of AA' equals to A'A
Apr
24
comment Is it possible for integer square roots to add up to another?
... and in this case, with $g = \gcd(x,y)$, we have $x = u^2 g$ and $y = v^2 g$ for some coprime integers $u,v$, i.e. the equation is $\sqrt{u^2 g} + \sqrt{v^2 g} = \sqrt{(u+v)^2 g}$.
Apr
24
comment Help to verify if this statement is correct?
What you mean is, if $x \in S \cap T \backslash \{0\}$ then $(P_S + P_T) x = 2x$, so the statement is false if $S \cap T \ne \{0\}$.
Apr
24
revised Help to verify if this statement is correct?
added 181 characters in body
Apr
24
answered Help to verify if this statement is correct?
Apr
23
answered How to use Maple's LLL Function to Break a Merkle-Hellman Knapsack
Apr
23
answered Compactness and Hausdorffness with different topology
Apr
23
revised Trouble with two equations with 4 unknowns
added 18 characters in body
Apr
23
comment Trouble with two equations with 4 unknowns
I didn't mean $y=b,x=a$. I meant there are two solutions: #1 with $x=0, y=b$, #2 with $x=a, y=0$.
Apr
23
answered Trouble with two equations with 4 unknowns
Apr
23
comment Trouble with two equations with 4 unknowns
Including $x=0$, $y = b$ and $x=a$, $y=0$?
Apr
23
comment Interchange of the expected value and infinite summation $E(\sum_{m=0}^\infty (it)^m Y_t^m/m!)=\sum_{m=0}^\infty E((it)^m Y_t^m/m!)$
If the distribution of the $J$'s is unknown, you can't assert convergence for the right side of your original equation except at $t=0$. You don't even know that $E[Y_t^m]$ exists at all.
Apr
23
answered How to come up with proofs of these results? Or, are these results true in the first place?
Apr
23
comment Interchange of the expected value and infinite summation $E(\sum_{m=0}^\infty (it)^m Y_t^m/m!)=\sum_{m=0}^\infty E((it)^m Y_t^m/m!)$
No, that's wrong. $E[Y_t^m] = \exp(\lambda t (E[J_1^m] - 1))$, not $\exp(\lambda t (E[J_1]^m-1))$.
Apr
23
comment Interchange of the expected value and infinite summation $E(\sum_{m=0}^\infty (it)^m Y_t^m/m!)=\sum_{m=0}^\infty E((it)^m Y_t^m/m!)$
The only way you could have $E[J_k^m] = c^m$ (and thus $E[Y_t^m] = e^{\lambda t (c^m-1)}$) for all $m$ is if $J_k = c$ with probability $1$.